Replication of the correlation between natural mood states and working memory-related prefrontal activity measured by near-infrared spectroscopy in a German sample - Sato, Hiroki; Dresler, Thomas; Haeussinger, Florian B.; Fallgatter, Andreas J.; Ehlis, Ann-Christine (Frontiers in Human Neuroscience, 2014)
Previous studies have suggested complex interactions of mood and cognition in the lateral prefrontal cortex (PFC). Although such interactions might be influenced by various factors such as personality and cultural background, their reproducibility and generalizability have hardly been explored. In the present study, we focused on a previously found correlation between negative mood states and PFC activity during a verbal working memory (WM) task, which had been demonstrated by using near-infrared spectroscopy (NIRS) in a Japanese sample. To confirm and extend the generalizability of this finding, we conducted a similar experiment in a German sample, i.e. participants with a different language background. Here, PFC activity during verbal and spatial WM tasks was measured by NIRS using a delayed match-to-sample paradigm after the participants’ natural mood states had been evaluated by a mood questionnaire (Profiles of Mood States: POMS). We also included control tasks to consider the general effect of visual/auditory inputs and motor responses. For the verbal WM task, the POMS total mood disturbance (TMD) score was negatively correlated with baseline-corrected NIRS data mainly over the left dorsolateral PFC (i.e., higher TMD scores were associated with reduced activation), which is consistent with previous studies. Moreover, this relationship was also present when verbal WM activation was contrasted with the control task. These results suggest that the mood–cognition interaction within the PFC is reproducible in a sample with a different language background and represents a general phenomenon.